Syntheses, and Crystal Structures of YIII Containing Di‐Metal Substituted 1, 5 Isomers of Heterometallic Tungstophosphate Nanoclusters: [Y{PM2W10O38(H2O)2}2]11– (M=CoII and ZnII). Issue 9 (1st March 2019) - Das, Vivek; Gupta, Rakesh; Iseki, Nao; Sadakane, Masahiro; Mougharbel, Ali S.; Kortz, Ulrich; Hussain, Firasat
Abstract: Two new Y III containing sandwich‐type heterometallic tungstophosphates: [Y{PM2 W10 O38 (H2 O)2 }2 ] 11– (M = Co II (1 ) and Zn II (2 )) have been synthesized under mild reaction conditions. Both the molecular complexes 1 a and 2 a were synthesized by reacting Y(NO3 )3 ⋅6H2 O, M(NO3 )2 ⋅6H2 O (M = Co II and Zn II ) with Wells‐Dawson type divacant K14 [P2 W19 O69 (H2 O)]⋅24H2 O precursor. The potassium salts of single crystalline material were collected and further used for characterization with different analytical techniques including single crystal X‐ray diffraction (SC‐XRD), Fourier transform infrared (FT‐IR) spectroscopy, inductively coupled plasma atomic emission spectroscopy (ICP‐AES), 31 P, 183 W and 89 Y nuclear magnetic resonance (NMR) spectroscopy, high‐resolution electro‐spray ionization mass spectrometry (HR‐ESI‐MS) as well as thermogravimetric analysis. Single crystal X‐ray diffraction analysis shows that both polyanions crystallize in the orthorhombic crystal system with space group Iba2 . Each polyanion consists of ( 1, 5 ) isomer of di‐metal substituted α‐Keggin type tungstophosphates, which sandwiched a Y III ion. Abstract : We have reported two new purely inorganic Y III containing di‐metal substituted sandwich‐type tungstophosphate nanoclusters [Y{PM2 W10 O38 (H2 O)2 }2 ] 11– (M=Co II (1 ) and Zn II (2 )) followed by one pot reaction procedure under mild reaction conditions. Both compounds were well characterized with different analytical techniques. The polyanion 1 and 2 consist of two units of ( 1, 5 ) isomers of di‐metal substituted hetero Keggin [PM2 W10 O38 (H2 O)2 ] 7– anion, sandwiched by yttrium ion.